Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning - Nataliia Zadyraka; Yevhen Leheza; Mykola Bykovskyi; Yevhenii Zheliezniak; Yulia Leheza (Jurnal Cita Hukum, 2023)
The purpose of the research is to identify the correlation between legal concepts of administrative Procedure and administrative liability in the sphere of urban planning. Main content. The regulatory basis for imposing administrative sanctions in the specified sphere consists of violating legislation, building regulations, standards, rules, etc. Methodology:  The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, as well as methods of analysis and synthesis. Conclusions. It is noted that the mechanism of bringing to administrative liability is based on a considerable number of legislative acts, building codes, standards, and rules, and this fact makes it much more challenging to understand this set of rules and contributes to their violation. Emphasis is placed on the fact that many offences in urban planning activities are detected during state architectural and construction control and supervision. Disclosed are some positions of the Supreme Court regarding the consideration and resolution of disputes related to appeals against resolutions on acceptable imposition. Peculiarities of implementation of norms of the institution of administrative liability in the sphere of urban planning activities for offenders of variable status have been revealed.